A three-dimensional semi-empirical model of a far turbulent wake. Issue 5 (2015) - Kaptsov, O.V.; Shmidt, A.V.
Abstract: A three-dimensional semi-empirical model of turbulence in the approximation of a far wake behind an axisymmetric self-propelled body is considered. The required quantities are the kinetic energy of the turbulence, the rate of dissipation of the kinetic energy of the turbulence, the mean density defect and the density fluctuation dispersion. A group-theoretic analysis is performed on the system of ordinary differential equations which is solved numerically. The solutions constructed are in good agreement with experimental data.